IMPROVING STUDENTS’ READING SKILL USING SELF AND PEER ASSESSMENT TECHNIQUE - Zuraida Zuraida (Jurnal Bahasa Lingua Scientia, 2012)
During the process of learning English as a foreign language, students often get difficulty in the classroom. It, then, strives the teacher to find an appropriate teaching method for better learning result. One of the skills which is considered to be difficult by the students of the second grade of MTs Nurul Huda Ngadirejo Blitar is reading. One teaching technique known as Self- and Peer- Assessment as part of the authentic assessment is considered to be effective to be applied in teaching reading in order to improve the students’ reading skill. The study aimed at knowing how Self- and Peer Assessment Technique can improve the students’ reading skill and how the students’ response toward the implementation of the technique is. The research design of the study was classroom action research with two cycles. The subject of this study was all of the second grade students of MTs Nurul Huda Ngadirejo. The instruments used to collect the data were test, observation sheet, field note, and questionnaire. In analyzing the data, the writer used descriptive qualitative and simple quantitative measurement to find out the result.